Pathogenetic substantiation of personified correction of folate cycle disorders using a complex with metapholine for the congenital malformations prevention - І. В. Руденко; В. П. Міщенко (Publishing House TRILIST, 2020)
Congenital malformations are pathology with a multifactorial etiology. Among their many endogenous, exogenous factors and hereditary predisposition are important. In particular a decrease in follicular enzymes (MTHFR, MTR, MTRR) activity at the genetic level, as well as a deficiency of vitamins and vitamin-like compounds of group B. Objective: to provide a pathogenetic justification for personified correction of disorders in the folate cycle in biological parents preparing for pregnancy to prevent congenital malformations in their children by using folates containing metafolin (5-MTHF). Materials and methods. The study involved 75 women and 75 men (biological parents) who had children/fetuses with congenital malformations in previous pregnancies, and 75 newborn children of these couples. All of them used the proposed preconceptional preparation. Alleles of folate cycle enzyme genes (MTHFR, MTR, MTRR) were determined by polymerase chain reaction in blood and saliva. Results. A high frequency of polymorphism of the folate cycle enzyme genes was observed in men among subjects (father, mother, child). The indicator was 77.7% compared with 68.7% in mothers and 60.7% in their children. The frequency of homozygous alleles was highest in parents (men) - 19.6%, lower in mothers - 13.1% and in children - 12.7%. Result of heterozygous alleles decreased from children indicator (87.3%) to their mothers (86.7%) and parents (80.4%). Conclusions. Obtained results emphasize the practical importance for determining the alleles of the folate cycle enzyme genes (MTHFR, MTR, MTRR) at the stage of preconception preparation for pregnancy in biological parents and then in their newborn children from the standpoint of preventive medicine. Reduced activity of the corresponding enzymes pathogenetically explains the feasibility of using folate complexes containing active folate metafolin (5-MTHF) in order to prevent congenital malformations.